Persistence of SARS-CoV-2 virus RNA in feces: A case series of children - Wenjun Du; Jinhong Yu; Xiaoyan Liu; Hong Chen; Lingbo Lin; Qiang Li (Elsevier, 2020)
Aims: To determine how long SARS-CoV-2 virus RNA persists in fecal specimens in children with COVID-19. Methods: Retrospectively, ten children with confirmed COVID-19 in the Jinan Infectious Disease Hospital Affiliated to Shandong University were enrolled between January 23, 2020 to March 9, 2020. Epidemiological, clinical, laboratory, and radiological characteristics of the children were analyzed. RT-PCR assays were performed to detect the SARS-CoV-2 virus RNA in the respiratory tract and fecal specimens in the follow-up after discharge. Results: Among ten patients, five (50%) were asymptomatic and five (50%) showed mild symptoms of respiratory illness. The average age of asymptomatic children was younger than that of symptomatic children (p = 0.03). The decreases in white blood cell (WBC) (p = 0.03) and lymphocyte (p = 0.03) counts were more severe in symptomatic patients than those in asymptomatic patients. During the follow-up examination after discharge, seven out of ten patients contained SARS-CoV-2 virus RNA in their fecal specimens, despite all patients showed negative results in respiratory tract specimens. One out of those seven patients relapsed. The median time from onset to being negative results in respiratory tract and fecal specimens was 9 days and 34.43 days, respectively. Conclusions: SARS-CoV-2 virus RNA persists much longer in the gastrointestinal (GI) tract than that in respiratory tract.